Genes and Pseudogenes: Complexity of the RCCX Locus and Disease - Carrozza, Cinzia; Foca, Laura; De Paolis, Elisa; Concolino, Paola (Frontiers in Endocrinology, 2021)
Copy Number Variations (CNVs) account for a large proportion of human genome and are a primary contributor to human phenotypic variation, in addition to being the molecular basis of a wide spectrum of disease. Multiallelic CNVs represent a considerable fraction of large CNVs and are strictly related to segmental duplications according to their prevalent duplicate alleles. RCCX CNV is a complex, multiallelic and tandem CNV located in the major histocompatibility complex (MHC) class III region. RCCX structure is typically defined by the copy number of a DNA segment containing a series of genes – the serine/threonine kinase 19 (STK19), the complement 4 (C4), the steroid 21-hydroxylase (CYP21), and the tenascin-X (TNX) – lie close to each other. In the Caucasian population, the most common RCCX haplotype (69%) consists of two segments containing the genes STK19-C4A-CYP21A1P-TNXA-STK19B-C4B-CYP21A2-TNXB, with a telomere-to-centromere orientation. Nonallelic homologous recombination (NAHR) plays a key role into the RCCX genetic diversity: unequal crossover facilitates large structural rearrangements and copy number changes, whereas gene conversion mediates relatively short sequence transfers. The results of these events increased the RCCX genetic diversity and are responsible of specific human diseases. This review provides an overview on RCCX complexity pointing out the molecular bases of Congenital Adrenal Hyperplasia (CAH) due to CYP21A2 deficiency, CAH-X Syndrome and disorders related to CNV of complement component C4.